2019
DOI: 10.15203/ciss_2019.013
|View full text |Cite
|
Sign up to set email alerts
|

Go soft or go home? A review of empirical studies on the role of self-compassion in the competitive sport setting

Abstract: Self-compassion describes a supportive attitude towards oneself. Research outside the sport context suggests that self-compassion might be beneficial in terms of psychological processes that are helpful for athletic performance. At the same time, there are reasons to assume that athletes may fear a negative influence of SC on their self-improvement motivation. Therefore, it seemed worthwhile to clarify the role of self-compassion in the competitive sport setting by reviewing the current research. A literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…This necessity also raises issues of the availability of support systems to HPCs and the responsibility professional organizations have for the training and development of coaches to work sustainably in their profession (Fletcher & Wagstaff, 2009). Finally, and in line with the general discussion points alluded earlier, we see a need for a range of applied intervention work for HPCs drawing on mindfulness (Longshore & Sachs, 2015;Lundqvist et al, 2018) and its effect on energy and mood (Pawsey et al, in press), how reflective practice is developed (Huntley et al, 2019) and how self-compassion may be cultivated (Mosewich et al, 2019;R€ othlin et al, 2019).…”
Section: Applied Implicationsmentioning
confidence: 72%
See 1 more Smart Citation
“…This necessity also raises issues of the availability of support systems to HPCs and the responsibility professional organizations have for the training and development of coaches to work sustainably in their profession (Fletcher & Wagstaff, 2009). Finally, and in line with the general discussion points alluded earlier, we see a need for a range of applied intervention work for HPCs drawing on mindfulness (Longshore & Sachs, 2015;Lundqvist et al, 2018) and its effect on energy and mood (Pawsey et al, in press), how reflective practice is developed (Huntley et al, 2019) and how self-compassion may be cultivated (Mosewich et al, 2019;R€ othlin et al, 2019).…”
Section: Applied Implicationsmentioning
confidence: 72%
“…Additionally, the participants noted that the SMS-diary prompted them to become aware of their "inner voice" (too often self-critical in nature) and its impact on wellbeing, which reflects another domain often addressed in compassion-focused therapy (Gilbert, 2009). While self-compassion has only recently received attention within elite sport and with focus on athletes (R€ othlin et al, 2019;Walton et al, 2020), the extant and emerging findings reported here relating to the perceived long-term positive behavior changes offer promising indications that self-compassion may help HPCs in their pursuit of sustainable well-being (c.f. Zessin et al, 2015).…”
Section: Discussionmentioning
confidence: 96%
“…Research on compassion-based interventions ( Neff, 2003 ; Gilbert, 2009 ) in sport is also scarce but is gaining interest ( Craig et al, 2020 ). However, despite an increased interest, a scoping review ( Röthlin, 2019 ) on the role of self-compassion in competitive sport settings only found one intervention study (i.e., Mosewich et al, 2013 ). Given the lack of empirical evidence, athletes experiencing mental health problems or disorders need to be included in future studies to evaluate the effectiveness of interventions based on CBT, ACT, or CFT.…”
Section: Psychotherapeutic Interventions In Sport Psychologymentioning
confidence: 99%
“…Previous literature reviews have focused on the concept of self-compassion within sport or physical activity in general. Röthlin et al (2019) did a scoping review of the published evidence on self-compassion research in competitive sport. They answered the question about whether self-compassion is beneficial to competitive athletes.…”
Section: Introductionmentioning
confidence: 99%
“…Another literature review on self-compassion and physical activity was conducted by Wong et al (2021) , focusing on self-care and differing from Röthlin et al’s (2019) study in that it looked at the general population rather than high-level performers. The authors highlighted that self-compassion was a trait allowing a positive and healthy self-care engagement.…”
Section: Introductionmentioning
confidence: 99%